The Burden of Pertussis in Low- and middle-income Countries since the Inception of the Expanded Programme on Immunization (EPI) in 1974: a systematic review protocol - Muloiwa, Rudzani; Kagina, Benjamin M.; Engel, Mark E.; Hussey, Gregory D (Systematic reviews, 2015)
Vaccine against pertussis has been in use for several decades. Despite the widespread use of pertussis vaccine, evidence shows resurgence of pertussis in high-income countries. Pertussis surveillance data is largely missing from low- and middle-income countries (LMICs). Without data on trends of pertussis, it is difficult to review and amend pertussis control policies in any country. We propose conducting a systematic review to evaluate the burden and trends of pertussis in LMICs since 1974.
Keywords: Pertussis; Whooping cough; Burden; LMICs